Roles of osmolality, calcium - Potassium antagonist and calcium in activation and flagellar beating pattern of sturgeon sperm - Alavi, S M H; Gela, D; Rodina, M; Linhart, O (Comparative biochemistry and physiology. Part A, Molecular & integrative physiology, 2011)
The present study shows the roles of osmolality, calcium (Ca(2+))-potassium (K(+)) antagonist and Ca(2+) in sperm activation and flagellar beating of a sturgeon species, sterlet (Acipenser ruthenus). Sperm motility was activated at hypoosmolality relative to seminal plasma and suppressed at 175 mOsmol kg(-1). Sperm activation was totally suppressed by 0.35mM K(+), but Ca(2+) could fully reverse K(+) inhibitory effect at Ca(2+): K(+) ratio of 0.25. Neither EGTA (a chelator of Ca(2+) ions) nor nifedipine (a Ca(2+) channel blocker) prevented sperm activation. But, sperm motility and velocity were significantly decreased by EGTA, nifedipine and an inhibitor for Ca(2+)/calmodulin activated phosphodiesterase (w-7) that suggest role of Ca(2+) signaling after triggering sperm activation through hypoosmolality. Symmetric flagellar beating was also turned to asymmetric after activation in w-7, which is an evidence for modulation of Ca(2+)-binding proteins activity. Sturgeon sperm, similar to salmonids, is immotile in seminal plasma due to high K(+) concentrations, but the mechanism of sperm activation seems to be closer to other fish species where osmolality prohibits sperm activation in seminal plasma. In these species, hypoosmolality is the primary signal for sperm Ca(2+)-dependent signaling of axonemal beating.
Keywords: Sperm Tail; osmolární koncentrace; Potassium; Calcium Channel Blockers; Egtazic Acid; Calcium-Calmodulin-Dependent Protein Kinases; draslík; EGTA; Sperm Motility; vápník; proteinkinasy závislé na vápníku a kalmodulinu; mužské pohlaví; chelátory; sulfonamidy; Osmolar Concentration; bičík spermie; blokátory kalciových kanálů; rybí proteiny; Calcium; nifedipin; Sulfonamides; zvířata; Chelating Agents; motilita spermií; Fishes; Nifedipine; ryby; Fish Proteins; Male; Animals